EFFECT OF PLANT DEFENSE INDUCERS ON POWDERY MILDEW AND NECROSIS OF SUNFLOWER (Journal of Plant Disease Sciences, 2024)
An investigation was carried out under field conditions during 2018-20 at Rabi Oilseeds Research Unit, Dr. Panjabrao Deshmukh Krishi Vidyapeeth, Akola to know the effect of salicylic acid as a plant defense inducer in the management of sunflower necrosis and powdery mildew disease. Statistically non significant difference was observed among the treatments towards germination. Seed treatment with salicylic acid @100 ppm and foliar spray with salicylic acid @100 ppm at 30 and 45 days after sowing (DAS) recorded minimum i.e. 1.70 and 2.35 per cent necrosis, respectively at one and two months after germination followed by seed treatment with salicylic acid @ 50 ppm and foliar spray with salicylic acid @ 50 ppm at 30 and 45 DAS i.e. 2.54 and 2.81 per cent necrosis, respectively at one and two month after germination. Minimum powdery mildew intensity was recorded by seed treatment with salicylic acid @100 ppm and foliar spray with salicylic acid @100 ppm at 30days and 45 DAS i.e. 8.22 and 16.22 per cent at one and two month after sowing. Seed treatment with salicylic acid @100 ppm and foliar spray with salicylic acid @100 ppm at 30 and 45 DAS recorded higher seed yield 1730 kg/ha followed by seed treatment with salicylic acid @ 50 ppm and foliar spray with salicylic acid @ 50 ppm at 30 and 45 DAS i.e. 1728 kg/ha. The control plot recorded lowest yield of 1059 kg/ha and highest disease incidence i.e. 7.88 and 9.13 per cent of powdery mildew and 30.68 and 41.44 per cent of necrosis at one and two month after germination, respectively. Seed treatment and foliar application of salicylic acid could protect the crop and minimize yield loss of sunflower due to necrosis and powdery mildew disease.
Keywords: Plant defense inducer; Powdery mildew; Necrosis; Salicylic acid; Sunflower